Prevalence and maternal risk factors of congenital malformations in newborns from Sergipe, Northeastern Brazil - Santos, Edna Josefa Nascimento (2022)
Introduction: Due to the importance of infant death caused by congenital malformations worldwide, more studies are necessary to determine the prevalence of these disorders serving as the basis for more effective control measures. Objective: To determine the prevalence and evaluate maternal risk factors for congenital malformations in newborns. Methods: A cross-sectional and retrospective study was performed in the reference maternity hospital for high-risk pregnancies in the state of Sergipe, northeastern Brazil. Data were collected from the medical records and declarations of live births of 16,518 births between January 2014 and December 2016, being included children with identified congenital malformations. Data were analyzed using the odds ratio, chi-square, and Fisher's exact test with p<0.05. Results: The study population was composed of 369 newborns with congenital malformations, which corresponds to 2.23% of total births. 53.9% were male, 47.9% had low birth weight and, 52.5% had adequate Apgar score. Anomalies affecting the musculoskeletal system were the most prevalent (30.9%), with polydactyly being the most frequent (53.5%). The number of prenatal consultations, education, and gestational age were the main observed maternal risk factors of congenital malformations. Anomalies of the circulatory system (OR=3.2 CI95% 1.3-7.84), multiple malformations (OR=9.24 CI95% 3.07-27.83), and chromosomal syndromes (OR=2.72 CI95% 1.48-5.01) were the most commonly associated with newborn deaths. Conclusion: The study presents the prevalence and risk factors related to malformations in the state of Sergipe, and improvements on maternal care and socioeconomic variables are important to decrease the number of malformations cases in Brazil.